Vibration Antiresonance Design for a Spacecraft Multifunctional Structure. (27th August 2017) - Li, Dong-Xu; Liu, Wang; Hao, Dong
Abstract : Spacecraft must withstand rigorous mechanical environment experiences such as acceleration, noise, vibration, and shock during the process of launching, satellite-vehicle separation, and so on. In this paper, a new spacecraft multifunctional structure concept designed by us is introduced. The multifunctional structure has the functions of not only load bearing, but also vibration reduction, energy source, thermal control, and so on, and we adopt a series of viscoelastic parts as connections between substructures. Especially in this paper, a vibration antiresonance design method is proposed to realize the vibration reduction. The complex zero-point equations of the vibration system are firstly established, and then the vibration antiresonance design for the system is achieved. For solving the difficulties due to viscoelastic characteristics of the connecting parts, we present the determining formulas to obtain the structural parameters, so that the complex zero-point equations can be satisfied. Numerical simulation and ground experiment demonstrate the correctness and effectiveness of the proposed method. This method can solve the structural vibration control problem under the function constraints of load bearing and energy supplying and will expand the performance of spacecraft functional modules.